The Effect of Work Stress on Nurse Performance in the Wijaya Kusuma Inpatient Room at Kediri Baptist Hospital - Pantawis, Kayoman ST Luhur (International Journal Labs, 2024)
Nurses are medical personnel and important pioneers in public health services in hospitals. To achieve the ideals and goals of the hospital, it is very important for the hospital to be able to maximize the performance of every employee, including nurses. Performance is the process and result of an activity carried out by employees with their capabilities to meet the standards or indicators set in an effort to support the company in achieving its goals. There are many variables that can influence performance, one of which is work stress. Nurses who experience emotional, mental and physical disorders caused by the work environment, workload and demands from superiors can be said to be experiencing symptoms of work stress. Nurses who have symptoms of work stress and do not have good stress coping mechanisms will tend to decrease their performance. The aim of this research is to find out how work stress influences the performance of nurses in the Wijaya Kusuma Inpatient Room at Baptist Kediri Hospital. This research uses quantitative research methods. The sampling method in this research used probability simple random sampling and used a sample of 33 people. The instrument and data collection in this research used a scale of perceptions of work stress (Robbbins & Judge, 2017) and performance (Koopsmans, 2014). In testing this hypothesis, the results obtained were R2 = 0.220 (p<0.05). These findings indicate that nurses in the Wijaya Kusuma Room at Baptist Hospital Kediri have a significant level of work stress which has an influence on performance.